Distance from referral hospital as a risk factor for mortality and length of stay of neonates admitted in a tertiary care hospital - Pandita, Kawal Krishen (International Journal Of Community Medicine And Public Health, 2019)
Background: Around 66% of infant and over 50% of under-five mortality occurs in newborn period. 99% of neonatal deaths occur in low and middle income countries. Most of these deaths can be prevented by suitable interventions at various levels. The premise of the study is that the neonates who require long transportation (>1 hour) have higher chances of mortality or prolonged stay in the hospital. Methods: A retrospective retrieval of data and prospective interview was conducted in G.B Pant children’s hospital Srinagar, an associated hospital of Govt. Medical College Srinagar in North India. Results: During the period of study 1431 neonates from twelve districts of the state were referred to the hospital for treatment, out of whom, 102 (7.13%) could not be saved. Neonatal death rate was found highest (11.11%) in neonates referred from districts of category-III (>100 kms from the referral hospital), followed by category-II (50-100 kms from the referral hospital) and category-I (>50 kms from the referral hospital). Average length of stay was observed longest for the neonates referred from districts of category-III followed by category-II and category-I. Conclusions: Several other studies found that transfer of sick neonates from another health facility were associated with relatively higher probability of morbidity and mortality after controlling for other predictors. Distance no doubt is a risk factor for neonatal outcome of referred neonates as we have observed in our study. To minimize neonatal deaths it is necessary to strengthen the perinatal services sick newborn care unit (SNCUs) in district Hospitals).